Across the great divides: Gender dynamics influence how intercultural conflict helps or hurts creative collaboration - CHUA, Roy Y. J. (Institutional Knowledge at Singapore Management University, 2020)
Collaborating across cultures can potentially increase creativity due to access to diverse ideas and perspectives, but this benefit is not always realized. One reason is that the conflict that arises in intercultural creative collaboration is a double-edged sword and how it is managed matters. In this research, we examine how the gender of collaborating dyads influences the link between intercultural conflict (task and relationship) and creative collaboration effectiveness. Through two studies (a laboratory study and a field survey), we found that intercultural task conflict has a negative effect on creative collaboration in men dyads but a positive effect on creative collaboration in women dyads. Conversely, intercultural relationship conflict has a negative impact on creative collaboration in general, but this effect is stronger for women than men dyads. These effects can be traced to how men versus women dyads handled intercultural conflict. There is also evidence that information elaboration (exchange, discussion, and integration of task-relevant information and ideas) mediates the effects of dyad gender and intercultural conflict on creative collaboration. These findings extend current understanding of when and how intercultural collaborations can result in creativity benefits from a gender and conflict management perspective.